PENENTUAN STRATEGI RANTAI PASOK UMKM YANG KOMPETITIF BERDASARKAN LOGISTICAL-CROSSFUNCTIONAL DRIVERS: STUDI KASUS UMKM DI KABUPATEN JOMBANG – JAWA TIMUR - Sumarsono, Sumarsono; Muflihah, Nur (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2021)
Pengembangan UMKM diperlukan, dengan cara penentuan strategi rantai pasok kompetitif. Penelitian ini bertujuan menentukan strategi rantai pasok UMKM yang kompetitif, dengan menganalisis kebaikan hasil prediksi, kemudian mengidentifikasi strategi kompetitif dari aspek fasilitas, inventori, transportasi (logistical drivers) dan dari aspek informasi, sourcing, pricing (crossfunctional drivers). Selanjutnya menganalis pengaruh tiap aspek tersebut terhadap strategi rantai pasok UMKM kompetitif. Desain penelitian menggunakan desain kuantitatif analitik, dengan data penelitian hasil survei dengan teknik purpose sampling, dan obyek studi kasus UMKM di Kabupaten Jombang Jawa Timur. Metode analisa data menggunakan Structural Equation Modelling-Partial Least Square (SEM-PLS). Hasil penelitian, bahwa kebaikan hasil prediksi berdasarkan evaluasi nilai R2 dan Q2 merupakan prediksi yang baik dan relevan untuk memprediksi. Selanjutnya hasil identifikasi strategi rantai pasok kompetitif dari aspek fasilitas, inventori, transportasi (logistical drivers) diketahui sekitar 30% sampai 40% UMKM yang memiliki arah strategi kompetitif. Kemudian dari aspek informasi, sourcing, pricing (crossfunctional drivers) diketahui sekitar 27%-33% UMKM dengan arah strategi kompetitif. Hasil analisis pengaruh aspek logistical-crossfunctional terhadap strategi rantai pasok UMKM yang kompetitif, disimpulkan semua aspek signifikan berpengaruh. Besarnya koefisien pengaruh terurut dari faktor fasilitas, sourcing, informasi, transportasi, inventori, dan pricing. Implementasi penelitian, dengan mengetahui jumlah UMKM belum kompetitif untuk selanjutnya agar dikembangkan, melalui penerapan prioritas urutan logistical-crossfunctional drivers. Abstract[Determining Competitive MSMEs Supply Chain Strategies Based on Logistical-Crossfunctional Drivers: A Case Study of MSMEs in Jombang Regency-East Java] The development of MSMEs are needed, by establishing a competitive supply chain strategy. This study aims to determine a competitive MSMEs supply chain strategy, by analyzing the goodness of the prediction, then identifying competitive strategies from the aspects of facilities, inventory, transportation (logistical drivers) and from the aspects of information, sourcing, pricing (cross-functional drivers). Furthermore, analyzing the influence of each of these aspects on the supply chain strategy of competitive MSMEs. The research design used a quantitative analytic design, with research data from the survey results using purposive sampling technique, and the object of the MSMEs case study in Jombang Regency, East Java. Methods of data analysis using Partial Least Square- Structural Equation Modeling (PLS-SEM). The results of the study, that the goodness of the prediction results based on evaluating the values of R2 and Q2is a good prediction and relevant to predict. Furthermore, the results of the identification of competitive supply chain strategies from the aspects of facilities, inventory, transportation (logistical drivers) are known that about 30% to 40% of MSMEs have a competitive strategy direction. Then from the aspect of information, sourcing, pricing (crossfunctional drivers), are known that about 27% -33% of MSMEs with a competitive strategy direction. Based on the analysis of the influence of each aspect of the supply chain strategy of competitive MSMEs, it is concluded that all aspects of logistical-cross-functional drivers are significant. The magnitude of the ordered influence coefficient is from the facilities, sourcing, information, transportation, inventory, and pricing. Research implementation, by knowing the number of MSMEs are not yet competitive, so that they are further developed, through the application of priority sequences of logistical-crossfunctional drivers.Keywords: Crossfunctional Drivers; Logistical Drivers; MSMEs Competitive Strategy; MSMEs Supply Chain; PLS-SEM